Evaluation and Correlation of Maxillary Sinus Mucosal Thickening with Periapical Lesions: A CBCT Study - Vatram, Sahithi Ram.; Raju. B, Mrudula; Prashanthi, Prashanthi; Deepthi, Buddha Syam; Poluri, Lakshmi Sasi; Gandhi, Vyshnavi Durga (Journal of Neonatal Surgery, 2025)
Introduction: Maxillary sinus is the principal paranasal sinus which assumes a pyramid-shaped depression within the maxilla, possessing a typical volume of 12.5 mL. During the culmination of dento-maxillo-facial development, the maxillary floor attains its definitive anatomical features, leading to a close spatial relationship between the teeth and the sinus floor. CBCT is the most widely used radiographic method for diagnosing maxillary sinus pathology due to its superior resolution in identifying both osseous and soft tissue structures. Aim: The aim of the present study is to assess the mucosal thickening of maxillary sinus and its relationship to periapical lesions. Materials & Methods: This academic study focuses on analyzing Cone Beam Computed Tomography (CBCT) scans from a cohort of 40 individuals. The research aims to identify apical lesions in posterior maxillary teeth, specifically related to sinus mucosal thickness, establish anatomical correlations between maxillary sinuses and teeth, and categorize these connections. Results: Class 4 mucosal thickening (4–10 mm) demonstrated the highest mean value (6.18 mm). A significant association was observed between periapical lesions and MT (p < 0.001), while gender had no significant influence (p = 0.298). Periapical abscesses and endo-Perio lesions were most frequently associated with sinus mucosal changes. Conclusion: Periapical pathology significantly influences sinus mucosal thickening. CBCT proves to be an invaluable diagnostic tool in evaluating sinus-dental relationships, aiding in clinical decision-making